Functional Analysis of Genetic Variations in Surfactant Protein D in Mycobacterial Infection and Their Association With Tuberculosis - Hsieh, Miao-Hsi; Ou, Chih-Ying; Hsieh, Wen-Yu; Kao, Hui-Fang; Lee, Shih-Wei; Wang, Jiu-Yao; Wu, Lawrence S. H. (Frontiers in Immunology, 2018)
Surfactant proteins A and D (SP-A and SP-D) are members of the collectin family and function in the clearance of infectious particles in the lungs. Some polymorphisms of surfactant proteins that give rise to amino acid changes have been found to affect their function. Several SP-A gene polymorphisms have been reported to be associated with respiratory infection diseases, such as tuberculosis (TB). However, the relationship between SP-D polymorphisms and TB is still unclear. In order to study the associations between SP-D polymorphisms and TB, the correlations of SP-D polymorphisms with TB were examined in a case-control study, which included 364 patients with TB and 177 control subjects. Additionally, we cloned two major SP-D exonic polymorphism C92T (rs721917) and A538G (rs2243639) constructs and used these for in vitro assays. The effects of SP-D polymorphisms on agglutination and other interactions with Mycobacterium bovis Bacillus Calmette-Guerin (BCG) were evaluated. In comparison with SP-D 92C (amino acid residue 16, Threonine), our results showed that SP-D 92T (amino acid residue 16, Methionine) had a lower binding ability to M. bovis BCG, a lower capacity to inhibit phagocytosis, lesser aggregation, poorer survival of BCG-infected MH-S cells, and less inhibition of intracellular growth of M. bovis BCG. The case-control association study showed that the 92T homozygous genotype was a risk factor for TB. However, a lesser effect was seen for polymorphism A538G. In conclusion, the results of functional and genetic analyses of SP-D variants consistently showed that the SP-D 92T variant increased susceptibility to TB, which further confirmed the role of SP-D in pulmonary innate immunity against mycobacterial infection.